2014
DOI: 10.3389/fphys.2014.00230
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function, health-related quality of life, and symptoms of depression and anxiety sensitivity are impaired in patients with the postural orthostatic tachycardia syndrome (POTS)

Abstract: The Postural Orthostatic Tachycardia Syndrome (POTS) is a condition in which heart rate increases abnormally when the individual assumes an upright position. In addition to the marked tachycardia, presyncope, and syncope, patients with POTS often complain of light-headedness, fatigue, and difficulty in concentrating. The present study assessed individuals with POTS for psychiatric comorbidity, anxiety sensitivity and health related quality of life and examined general cognitive ability. Data was obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 45 publications
4
77
3
Order By: Relevance
“…The high prevalence of headaches identified is in keeping with a retrospective evaluation of symptoms in paediatric patients presenting to a POTS clinic . The autonomic symptoms associated with POTS can negatively impact many aspects of daily life including cognitive function, sleep, energy levels and the ability to exercise, work and attend school . A history of syncope was reported in only 36% of survey participants, which is much lower than that reported in the smaller POTS UK study (58%) .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The high prevalence of headaches identified is in keeping with a retrospective evaluation of symptoms in paediatric patients presenting to a POTS clinic . The autonomic symptoms associated with POTS can negatively impact many aspects of daily life including cognitive function, sleep, energy levels and the ability to exercise, work and attend school . A history of syncope was reported in only 36% of survey participants, which is much lower than that reported in the smaller POTS UK study (58%) .…”
Section: Discussionsupporting
confidence: 65%
“…When formally assessed, POTS patients have no increased lifetime prevalence of psychiatric disorders as compared to the general population, and POTS patients have mental health scores similar to national norms whether they have improved or not 5 years after diagnosis . However, other studies have also suggested that patients with POTS may have increased prevalence of depression and anxiety . It is unknown how much of the psychological health problems that exist in POTS patients may be due to living with a chronic medical illness or exacerbated by the stressful prolonged diagnostic process and misdiagnosis the majority of POTS patients experience.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this latter study, the level of depression was quite high, with a mean BDI score of 15. Although studies have shown that depression impacts negatively on cognitive performance and QoL in patients with orthostatic intolerance [39] and that the placebo effect on SF-36-MCS scores is substantially increased in patients with depression [32], we found no significant association between baseline symptoms of depression and the change in SF-36 MCS score.…”
Section: Discussioncontrasting
confidence: 80%
“…Some studies have demonstrated no differences in incidence for major depression, anxiety, or substance abuse disorders between POTS patients and the general population . On the other hand, Anderson et al noted significantly higher depression and anxiety scores in patients with POTS. These differences may be due to the differences in methodology employed in these assessments, requiring additional work to know if psychological conditions should also be routinely assessed in the POTS patient.…”
Section: Introductionmentioning
confidence: 99%